Identification of Two Homozygous Sequence Variants in the COL7A1 Gene Underlying Dystrophic Epidermolysis Bullosa by Whole‐Exome Analysis in a Consanguineous Family. (23rd June 2015) - Serafi, Rehab; Jelani, Musharraf; Almramhi, Mona M.; Mohamoud, Hussein S.A.; Ahmed, Saleem; Alkhiary, Yaser M.; Zhang, Jianguo; Yang, Huanming; Al‐Aama, Jumana Y.
Summary Dystrophic epidermolysis bullosa (DEB) is an inherited skin disorder with variable severity and heterogeneous genetic involvement. Diagnostic approaches for this condition include clinical evaluations and electron microscopy of patients' skin biopsies, followed by Sanger sequencing (SS) of a large gene (118 exons) that encodes the alpha chain of type VII collagen (COL7A1) located on Chromosome 3p21.1. However, the use of SS may hinder diagnostic efficiency and lead to delays because it is costly and time‐consuming. We evaluated a 5‐generation consanguineous family with 3 affected individuals presenting the severe generalised DEB phenotype. Human whole‐exome sequencing (WES) revealed 2 homozygous sequence variants: the previously reported variant p.Arg578* in exon 13 and a novel variant p.Arg2063Gln in exon 74 of the COL7A1 gene. Validation by SS, performed on all family members, confirmed the cosegregation of the 2 variants with the disease phenotype. To the best of our knowledge, 2 homozygous COL7A1 variants have never been simultaneously reported in DEB patients; however, the upstream protein truncation variant is more likely to be disease‐causing than the novel missense variant. WES can be used as an efficient molecular diagnostic tool for evaluating autosomal recessive forms of DEB.